FEATURES OF THE CLINICAL COURSE OF LOCAL HYPOPLASIA OF HARD DENTAL TISSUE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Local hypoplasia can result from various etiological factors, including systemic diseases, dental development disorders, or localized trauma. The timing of the stroke during dental development may influence the severity and extent of hypoplastic defects. It may be associated with systemic diseases and have functional and psychological consequences. Diagnosis involves a thorough examination of the affected teeth, and treatment options range from minimally invasive approaches to full-blown restorations. Long-term monitoring, maintenance, and interdisciplinary collaboration may be required. This article highlights the importance of patient education and counseling and highlights the need for ongoing research in this area.